A reading of the montage-based advocacy study of Andalusian muwashshahat - Kemache, bilal; malkia, belkacem (El Omda in Linguistics and Discourse Analysis, 2024)
This article attempts to investigate the concept of Andalusian stanzas, and seeks to clarify the dialectical and deconstructive vision of Izz al-Din al-Manasra, and the various concepts of stanzas and their various problems, in addition to addressing the most important issues from a montage perspective.